Exploring the interactions of rapamycin with target receptors in A549 cancer cells: insights from molecular docking analysis - Sanjeev K. Ganesh; C. Subathra Devi (Journal of Cancer Research and Clinical Oncology)
Abstract Rapamycin, a macrocyclic antibiotic derived from the actinomycetes Streptomyces hygroscopicus, is a widely used immunosuppressant and anticancer drug. Even though rapamycin is regarded as a multipotent drug acting against a broad array of anomalies and diseases, the mechanism of action of rapamycin and associated pathways have not been studied and reported clearly. Also reports on the binding of rapamycin to cancer cell receptors are limited to the serine/threonine protein kinase mTORC1. Hence, to uncover the exact potential of rapamycin in cancer therapy, a series of cell culture and in silico studies were conducted to identify other receptors capable of binding to rapamycin. Through molecular docking and simulations, it was found that the receptors EGFR, FKBP12, MET, FGFR, ROS1 and ALK were capable of binding with rapamycin. The findings from the current study provides new insights in modern cancer research and therapy. This could also facilitate in understanding the possible action mechanisms of rapamycin in other diseases such as neurovegetative diseases, autoimmune diseases, etc.